Indigenous legume fodder trees and shrubs with emphasis on land use and agroecological zones: Identification, diversity, and distribution in semi‐humid condition of southern Ethiopia. Issue 5 (6th June 2022) - Abraham, Getachew; Kechero, Yisehak; Andualem, Dereje; Dingamo, Temesgen
Abstract: Background: Fodder trees and shrubs are among the strategic feed resources that complement the dry season feed supply in the tropics. They are an integral element of the farming system incorporated into different land uses and deliver multiple functions, even though their diversity relies on various anthropogenic, physiographic, and agroecological factors. Objective: The study aimed to identify indigenous legume fodder trees and shrubs (ILFTS) and estimate their diversity in terms of land use and agroecological zones in southern Ethiopia's Gamo landscape. Method: Respondent households were selected using a stratified multistage sampling procedure. Information about the ILFTS was gathered through key informant interviews conducted in each agro‐ecological zone. A total of 273 households from three agro‐ecological zones were selected and interviewed using a semi‐structured questionnaire to assess ILFTS. The information acquired by the questionnaire survey was complemented with a focus group discussion held with 10 respondents in each agro‐ecological zone. Herbarium samples were collected for each of the species for identification and confirmation of the botanical names. Sixty randomly selected sampling plots of each with a dimension of 20 m × 20 m were created, and inventories of ILFTS species were performed and recorded on species inventory sheets. The Shannon–Wiener diversity index ( H ) was used to determine the species diversity. Result: The study identified 21 ILFTS that have been an integral constituent of the land uses recognised for their multiple functions in all agroecological zones. The mean species richness and diversity indices of the ILFTS differed significantly with land use and agroecological zones, where the lowland area closure exhibited the highest, and the highland homesteads and highland grazing land revealed the least. Conclusion: Farmers' indigenous knowledge and previous experience determined the species richness and diversity of ILFTS in farmlands and homesteads; however, the level of exploitation or protection was the reason for variation in area closure and grazing lands.